STRATEGI PENINGKATAN PEMASARAN DAN PENJUALAN PRODUK OLAHAN BUAH MANGROVE MELALUI PEMBUATAN WEBSITE - Ubaidillah Umar; Aulia Rahma Annisa; Helmy Widyantara (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Besides being useful for protecting the coast from abrasion, mangrove plants have many other benefits, one of which is the fruit of the mangrove plant. The fruit of this mangrove plant was successfully processed by one of the UKM residents of Medokan Ayu Surabaya, namely "UKM Somano," which utilizes the fruit of the mangrove plant into several processed food and beverage products that have many benefits and are in great demand by the wider community. UKM Somano is indeed considered to have succeeded in making an innovation in processed food and beverage products derived from punch fruit, but in reality, UKM Somano has problems marketing their processed products. So far, Somano's products are only well known through Instagram and the marketplace, but not many people know about Somano's SME products. Therefore, this research proposal proposes the creation of a website and assistance to UKM Somano in terms of digital literacy that contains business profiles of UKM Somano and displays various products processed from mangrove fruit. With the creation of a website and digital literacy assistance for Somano SMEs, it is hoped that more and more members of the general public will know that mangrove fruit can be processed into various superior product innovations and can help increase the amount of production by Somano SMEs.